Seafood Allergy - Laoaraya, Mongkol (Biomedical Sciences and Clinical Medicine, 2016)
Seafood plays an important role in human nutrition worldwide. The increased production and consumption of seafood has been accompanied by more frequent reports of adverse health problem. The epidemiological data from Thailand highlight seafood as one of the most common causes of food hypersensitivity. The diagnostic approach may require further investigations such as skin prick test, serum specific immunoglobulin E for screening before a food challenge. In contrast to cow’s milk and egg, allergies to seafood are usually not outgrown. The proven therapy is strict avoidance. The recent extensive efforts have revealed the allergen characterizations and immunological properties of major fish and shellfish allergens, which are parvalbumin and tropomysin, respectively. Current observations demonstrated the molecular and clinical cross-reactivity within the fish family and between different species of shellfish and other invertebrates such as house dust mites and cockroach. Future research on immunological and clinical seafood allergy will improve diagnosis, management and the development of effective and life-long allergenspecific immunotherapy.